Genes and Cancer - Lemamy, Guy-Joseph (IntechOpen, 2019)
Cancer is a malignant tumor caused by DNA damage, which leads to uncontrolled cell growth. Tumor progression is locally favored by the mitogenic effects of hormones or growth factors, which stimulate the tumor's growth, or the activation of vascular endothelial growth factor receptor, which induces angiogenesis and leads to metastasis. About 300 out of 25,000 genes that set up the human genome are involved in cancer pathology. These genes are divided into three groups: oncogenes, tumor suppressor genes, and DNA repair genes. Activated oncogenes promote the development of cancer, whereas the tumor suppressor and DNA repair genes have a protective role by respectively inhibiting cell cycle progression and inducing apoptosis, or by repairing DNA damage occurring during the cell cycle. This book discusses the issue of tumor suppressor genes through chapters written by experts using advanced biochemistry, cell, and molecular biology tools. The tumor suppressor genes can be used as markers of risk to identify populations with high risk or targets for cancer treatment and therapeutic resistance. We hope that the work provided in this book will be useful for researchers and students and will increase knowledge of the understanding of cancer and improve its treatment.